Cognitive impairment in Parkinson's disease - Verbaan, D (BMJ Group, 2007)
BACKGROUND: Cognitive impairment plays a role in Parkinson's disease (PD) and has important consequences for patient management. However, many aspects of cognitive impairment in PD remain unclear because of the use of different and often invalid measurement instruments. In this study, a reliable and valid instrument, the SCales for Outcomes in PArkinson's disease‐COGnition (SCOPA‐COG), was used. AIM: To evaluate cognitive functioning in a large cohort of patients with Parkinson's disease and to assess the relations with demographic, disease related and clinical variables. METHODS: A cohort of 400 patients with PD was evaluated for cognition, motor and non‐motor domains, as well as for demographic and disease related characteristics. Results were compared with 150 controls matched for overall age, sex and education distribution. RESULTS: Patients with PD scored significantly lower on all cognitive subdomains compared with controls, with the largest differences for executive functioning and memory. After correction for age and years of education, 22% of patients had impaired cognition, as measured by the total SCOPA‐COG score, compared with controls. Across all patients, more severe cognitive impairment was associated with significantly more impairment in motor, autonomic, depressive and psychotic domains. Patients with the postural instability gait difficulty (PIGD) dominant phenotype showed more cognitive impairment compared with patients with the tremor dominant phenotype. Contrary to tremor scores, PIGD scores significantly worsened with increasing disease severity. CONCLUSIONS: Cognition is an important domain of the clinical spectrum of PD and poorer cognitive performance is associated with greater impairment in motor and non‐motor domains in PD. The difference in cognitive scores between PIGD dominant patients and tremor dominant patients likely reflects more advanced disease.